Contextualising the Islamic fundamentals in the contemporary concepts of sustainability, livability and quality of life in the built environment - Ahmad Sarkawi, Azila; Abdullah, Alias (IDOSI Publications, 2015)
Islam is a regulatory religion. It prescribes fundamental principles to every spectrum of human life including the built environment. Sustainability, livability and quality of life have become catch terms in the built environment field nowadays. Despite their well formulated objectives, these concepts are not free from criticisms for their inconsistencies, ambiguities, vagueness and lacked basis. Viewing these three concepts concurrently gives rise to the observations that the concepts are overlapped and difficult to measure as there is no ‘one-size fits all’ indicators. Thus, the paper aims to address their shortcomings by contextualising these three concepts within the ambit of Islam. Subsequently, the interpretation of these terms from various scholars and organizations is analysed using content analysis. Their commonalities and differences are identified and discussed within the realm of the built environment. Consequently, these findings on commonalities and differences among sustainability, livability and quality of life and their conceptual reviews are being put into the context of religion that is in this case, Islam. An Islamic conceptual model is finally proposed with regard to these three concepts; relating them to the idea of the Islamic built environment and the value of life.